2019
DOI: 10.1158/1078-0432.ccr-18-2661
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rigosertib for the Treatment of Recessive Dystrophic Epidermolysis Bullosa–Associated Squamous Cell Carcinoma

Abstract: Purpose: Squamous cell carcinoma (SCC) of the skin is the leading cause of death in patients with the severe generalized form of the genetic disease recessive dystrophic epidermolysis bullosa (RDEB). Although emerging data are identifying why patients suffer this fatal complication, therapies for treatment of RDEB SCC are in urgent need. Experimental Design: We previously identified polo-like kinase 1 (PLK1) as a therapeutic target in skin SCC, including RDEB SCC. Here, we undertake a screen of 6 compounds ori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Although the drug was well-tolerated by 20 patients, no further studies were conducted. Preclinical work identified the potential of the multikinase inhibitor rigosertib, an experimental therapeutic in phase III trials for treatment of myelodysplastic syndrome and RDEB SCC [90]. In cell culture and animal studies, rigosertib induced apoptosis in RDEB SCC without adversely affecting non-SCC RDEB epidermal keratinocytes.…”
Section: Therapies For Eb-associated Squamous Cell Carcinomamentioning
confidence: 99%
“…Although the drug was well-tolerated by 20 patients, no further studies were conducted. Preclinical work identified the potential of the multikinase inhibitor rigosertib, an experimental therapeutic in phase III trials for treatment of myelodysplastic syndrome and RDEB SCC [90]. In cell culture and animal studies, rigosertib induced apoptosis in RDEB SCC without adversely affecting non-SCC RDEB epidermal keratinocytes.…”
Section: Therapies For Eb-associated Squamous Cell Carcinomamentioning
confidence: 99%
“…Animals that were grafted with RDEB patient-derived cSCCs and FB developed tumors within 2-3 weeks post-grafting with characteristic morphological features of human RDEB-cSCCs, as shown by H&E and immunofluorescence (IF) staining (Fig 1 b, c, d). Several studies have previously reported tumor xenograft mouse models using multiple RDEB SCC cells lines, zebrafish models and organ culture graft models for RDEB (Atanasova et al, 2019;Dayal et al, 2020;Martins et al, 2016;Watt et al, 2011). The concept of grafting skin equivalents onto immunodeficient mice has been reported previously (Breitkreutz et al, 1998;Martins et al, 2016;Willhauck et al, 2007).…”
Section: Letter To the Editormentioning
confidence: 99%
“…Rigosertib: Squamous cell carcinomas (SCC), one of the most threatening co-pathologies in RDEB, is treated with Rigosertib, a polo-like kinase (PLK)-1 inhibitor leading to apoptosis in cancer cells [86]. Oral and i.v.…”
Section: Further Small Molecule Drugs In Currently Ongoing Clinical Tmentioning
confidence: 99%